INCREASING PROFESSIONAL COMPETENCE OF TEACHERS OF PRIVATE VOCATIONAL SCHOOL IN KENDAL REGENCY THROUGH THE PREPARATION OF SCIENTIFIC ARTICLES OF CLASS ACTION RESEARCH - Murwatiningsih; Joko Widodo; Nina Oktarina; Edy Suryanto (STKIP PGRI Sidoarjo, 2022)
Continuous professional development is the development of teacher competencies that is carried out according to needs, continuously improving their professionalism. One type of continuous professional development is scientific publications in the form of research results or scientific ideas in the field of education. The purpose of community service activities is to improve the competence of professional teachers through the preparation of scientific articles resulting from classroom action research. This community service activity targets 25 teachers of Private Vocational Schools in the Kendal Regency. The method of activity used in this community service is the lecture method, question and answer, and discussion. Based on the series of activities that have been carried out, all participants can be actively involved in the discussions of the three main activities. This activity can improve the knowledge and skills of participants to compile articles from the results of classroom action research.